2008
DOI: 10.1063/1.2900123
|View full text |Cite
|
Sign up to set email alerts
|

On the reconstruction of a magnetosphere of pulsars nearby the light cylinder surface

Abstract: A mechanism of generation of a toroidal component of large scale magnetic field, leading to the reconstruction of the pulsar magnetospheres is presented. In order to understand twisting of magnetic field lines, we investigate kinematics of a plasma stream rotating in the pulsar magnetosphere. Studying an exact set of equations describing the behavior of relativistic plasma flows, the increment of the curvature drift instability is derived, and estimated for 1s pulsars. It is shown that a new parametric mechani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…2003; Osmanov et al. 2008). It was demonstrated that the magnetic field lines after the light-cylinder region transform into the Archimedes spiral with the step that provides the force-free regime, when the particles do not feel the influence of the magnetic field and, consequently, the rotation of the pulsar. The plasma mechanism of generation of drift waves and the growth of magnetic perturbations across the pulsar magnetic field was considered, which causes the magnetic field reconstruction near the light cylinder.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2003; Osmanov et al. 2008). It was demonstrated that the magnetic field lines after the light-cylinder region transform into the Archimedes spiral with the step that provides the force-free regime, when the particles do not feel the influence of the magnetic field and, consequently, the rotation of the pulsar. The plasma mechanism of generation of drift waves and the growth of magnetic perturbations across the pulsar magnetic field was considered, which causes the magnetic field reconstruction near the light cylinder.…”
Section: Resultsmentioning
confidence: 99%
“…2003; Osmanov et al. 2008). It was demonstrated that the magnetic field lines after the light-cylinder region transform into the Archimedes spiral with the step that provides the force-free regime, when the particles do not feel the influence of the magnetic field and, consequently, the rotation of the pulsar.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations